2006
DOI: 10.1097/01.brs.0000217686.80327.e4
|View full text |Cite
|
Sign up to set email alerts
|

Open Reduction of Irreducible Atlantoaxial Dislocation by Transoral Anterior Atlantoaxial Release and Posterior Internal Fixation

Abstract: This series has demonstrated the safety and efficacy of the transoral anterior atlantoaxial release in the reduction of IAAD. Most of the so-called irreducible/fixed AAD could become reducible after anterior release without odontoid resection. The posterior short-segment atlantoaxial or occipitocervical fixation, especially the plate screw instrumentation, could achieve further reduction and provide immediate stabilization. One-stage anterior release and posterior instrumentation and fusion are a safe and reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
147
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(151 citation statements)
references
References 22 publications
0
147
0
4
Order By: Relevance
“…Various congenital osseous anomalies at the craniocervical junction have been reported [11][12][13][14][15][16][17][18][19][20][21]. In the current study, the congenital lesions include os odontoideum, occipitalization of the atlas, congenital C2-3 fusion, congenital atlantoaxial subluxation, congenital basilar invagination and combined anomalies.…”
Section: Discussionmentioning
confidence: 75%
“…Various congenital osseous anomalies at the craniocervical junction have been reported [11][12][13][14][15][16][17][18][19][20][21]. In the current study, the congenital lesions include os odontoideum, occipitalization of the atlas, congenital C2-3 fusion, congenital atlantoaxial subluxation, congenital basilar invagination and combined anomalies.…”
Section: Discussionmentioning
confidence: 75%
“…A meaningful number of subtypes of C2-fractures exists where complete reduction, normal C1-2 rotation and a physiological anatomy is difficult to restore [1,10,11,34,42,43,71,82]. Likewise, a non-anatomical posttreatment C2-alignment, resembling a malunion, can cause significant symptoms even indicating fusion C1-2 [13,26,30,42,47,51,52,67,70,71,78,79] as it had to be done in one of our cases (Fig. 3), two others being scheduled (Fig.…”
Section: Malunion Of C2mentioning
confidence: 88%
“…The reduction can be maintained and further achieved by posterior fixation. In Wang's series of 33 IAAD cases [9], 26 (79%) obtained complete anatomical reduction. Some authors reported similar result but with anterior release and anterior fixation.…”
Section: Anterior Reductionmentioning
confidence: 97%
“…Without early intervention, instability at this segment may progress to dislocation. Dislocations that can be reduced by using skull traction are referred to as reducible atlantoaxial dislocations, while those dislocations that are unable to be reduced with skeletal traction, even with the assistance of general anesthesia and complete muscle relaxation, are referred to as fixed or irreducible atlantoaxial dislocation (IAAD) [9].…”
Section: History Diagnostic Differential Diagnosis Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation